Fighting for the Faith: Pierre du Moulin's polemical quest - Borvan, D (2019)
This thesis examines Roman Catholic and Reformed Protestant polemics in the early decades of the seventeenth century through the lens of the ecclesiastical activity and polemical method of Pierre du Moulin (1568–1658), with a particular focus on his treatise debate with Cardinal Jacques Davy du Perron (1556–1618). I argue that in his early polemical writings and debates, du Moulin displayed respect for the Church Fathers and church tradition but also showed a willingness to be openly critical of the Fathers when warranted. During this period, du Moulin staunchly displayed his firm ecclesiastical commitment to the French Reformed churches. However, du Moulin’s ecclesiastical activity and polemical methodology shifted after 1610 when he gained international recognition. In that year, du Moulin wrote in defence of King James VI and I of Scotland and England and inserted himself into the Oath of Allegiance controversy. After James expressed dissatisfaction with du Moulin’s handling of the Church Fathers in the volume, the French pastor softened his approach. His subsequent works, particularly those written on behalf of James, critiqued the Fathers in a more veiled manner. Du Moulin also altered his ecclesiastical activity after 1610 by becoming more ecumenical, partnering with King James in an effort to reunite Christendom. In a surprising move for a Calvinist, du Moulin initially accommodated Arminians in his plan for reunion, but shifted his position during the leadup to the Synod of Dort. Du Moulin also attempted to remain loyal to the French Reformed churches and their presbyterian government while maintaining his patronage relationship with King James, a strong supporter of episcopal polity. Though primarily a work of intellectual history, this thesis also places du Moulin’s ecclesiastical activity and polemical treatises in the broader political and ecclesiastical currents of both France and early Stuart England during the first three decades after the promulgation of the Edict of Nantes.